Rapid Access to cis-1,3-Dialkylindanes: Asymmetric Formal Syntheses of epi-Mutisianthol and epi-Jungianol - Tran, Cong So; Yoon, Moonsang; Le, Long Duc; Kim, Seoyeong; Kim, Huiae; Kim, Jisu; Nguyen, Long Huu; Koh, Minseob; Yun, Hwayoung (Synthesis, 2024)
Concise and strategically unique asymmetric formal syntheses of epi-mutisianthol and epi-jungianol are presented. A novel disconnection approach is introduced to complement previous intramolecular cyclopentannulation strategies. Noteworthy features include: (a) control of the stereogenic benzylic carbon center through 1,3-chirality transfer from chiral indenols via the Johnson–Claisen rearrangement, which yields advanced indene-containing γ,δ-unsaturated esters, and (b) the diastereoselective construction of the cis-1,3-dialkylindane backbone via catalytic hydrogenation of the resulting indene. This approach presents a remarkable method for synthesizing structurally intriguing indane motifs.
Keywords: epi-mutisianthol; epi-jungianol; cis-1,3-dialkylindane; Johnson–Claisen rearrangement; chirality transfer